Discretionary Projects Supported by the Office of Special Education Programs under the Individuals with Disabilities Education Act, Fiscal Year 1999 Personnel Preparation - Orkwis, Ray.; DeCarme, Judi; Glover, Jeanne; ERIC Clearinghouse on Disabilities and Gifted Education; Council for Exceptional Children, Reston, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1999)
This directory is one of five which together describe almost 1200 discretionary grants and contracts currently supported by the Research to Practice Division of the Office of Special Education Programs under the 1997 Amendments to the Individuals with Disabilities Education Act (IDEA). This document covers grants and contracts in the program area of Personnel Preparation. The program descriptions are grouped by the 13 competitions under which they were funded, including: Preparation of Special Education, Related Services, and Early Intervention Personnel To Serve Infants, Toddlers, Children, and Youth with Low-Incidence Disabilities; Preparation of Leadership Personnel; Preparation of Minority Personnel; Preservice Personnel Training; Special Projects; Improving the Preparation of Personnel To Serve Children with High-Incidence Disabilities; Projects of National Significance; Partnerships To Link Personnel Training and School Practice; and Special Olympics. Provided for each project description is the following information: grant number; project title; name of project director; contact information (organization, address, phone number, Fax number, e-mail address); the project's purpose; the methodology; and proposed products. There are four indexes: a project director index, an organization index, a state index, and a subject index. (DB)
Availability: Council for Exceptional Children, 1920 Association Drive, Reston, VA 20191-1589 (Stock No. R5350, $9 plus postage and handling). Tel: 888-232-7733 (Toll Free); Web site: http://www.cec.sped.org.
Sponsoring Agency: Special Education Programs (ED/OSERS), Washington, DC.
Contract Number: ED99CO0026.
ERIC Note: For the 1998 report, see ED 426 562; for related 1999 volumes, see EC 307 640-644.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Contracts; Disabilities; Early Childhood Education; Elementary Secondary Education; Federal Aid; Federal Programs; Grants; Infants; Leadership; Minority Groups; Pupil Personnel Services; Research and Development; Special Education Teachers; Teacher Education; Theory Practice Relationship; Toddlers; Office of Special Education Programs; Individuals with Disabilities Educ Act Amend 1997; Reference Materials, Directories/Catalogs.